Three dimensional self-assembly ZnSb nanowire balls with good performance as sodium ions battery anode. (1st September 2016) - Liao, S.; Sun, Y.; Wang, Jing; Cui, H.; Wang, Chengxin
Abstract: Novel 3D ZnSb nanowire balls composed of ultra-thin nanowires were achieved through simple self-assembly method based on typical thermodynamics in chemical vapor deposition (CVD) system. The elliptic cylinder-shaped nanowires with cross-section size of ∼25nm × ∼ 10 nm display impressive performance in sodium-ion battery (SIB) application as anode material. Comparing to pure Sb, ZnSb is advantageous in resisting huge volume change and possess enhanced conductivity, which would do much better to offer a long-time cycling stability and rate performance. Such a small size of the low dimensional structures can further improve the electron/ion transfer efficiency. Through systematic measurements, we found that, at 20 mA/g, the capacity remains 377mAh/g after the 100th cycle with the coulombic efficiency at ∼99%. Even if the current density increased to 750 mA/g, the value was still higher than 225mAh/g. The half-cell device also provides a rapid response and stable output in the rate tests (20–650 mA/g). The good performance originates from the unique structural configuration, implying the huge potential value of ZnSb in SIB application. We hope the results also can expand the Sb based anode material family.